The role of organizational culture on sustainable construction among Malacca Malaysian Construction Industry: A partial least square approach - Subani, N.A.; Adeleke, A. Q.; Bamgbade, J.A. (International Society for Everant Publisher, 2020)
This research studies the influence of organizational culture on sustainable construction among G7 contractors operating in Malacca, Malaysia. As there are opinions buttressing the need to integrate culture that reinforces devotion towards sustainability in an organization so as to ensure a successful sustainability adoption in project’ activities. Therefore, in response to this apprehension, the objectives of this study are to investigate the significant relationship between adhocracy culture and environmental protection and to investigate the significant relationship between hierarchical culture and environmental protection. To achieve this, quantitative research was conducted with a proportionate stratified random sampling used to choose 100 construction companies mainly G7 that are registered under the Construction Industry Development Board (CIDB) Malaysia operating in Malacca. A total of 90 valid and completed questionnaires were returned representing a 90% response rate. The validity, as well as the reliability of the items in this research, were assessed using the PLS-SEM measurement model and it shows that the results are reliable. The two hypotheses were tested and the result showed that adhocracy culture (AC) variable has a significant positive relationship on sustainable construction (β= 0.525, t = 3.722, p = 0.000) as organizational culture with dynamism, which is represented by adhocracy is concluded to be influential in sustainability, and also play a critical role in a society in the context of sustainability and corporate citizenship. Implications for practice and future research were also discussed.